Surgical management of Giant paraclinoid internal carotid artery aneurysm management in Endovascular era - Jha, Prabhat; jha, Binit kumar; Bohara, Manoj; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2021)
Giant aneurysms are lesions with diameter greater than or equal to 25 mm. They are uncommon lesions presenting with features of mass effect and rarely rupture. Diagnosis confirmed on angiography.This case describes a young female with giant paraclinoid internal carotid artery aneurysm. The patient was managed with superficial temporal artery to middle cerebral artery bypass with aneurysm trapping.KeywordsGiant aneurysm, STA-MCA bypass, aneurysm trapping